Viral diversity and blood-feeding patterns of Afrotropical Culicoides biting midges (Diptera: Ceratopogonidae) - Ogola, Edwin O.; Bastos, Armanda D. S.; Slothouwer, Inga; Getugi, Caroline; Osalla, Josephine; Omoga, Dorcus C. A.; Ondifu, Dickens O.; Sang, Rosemary; Torto, Baldwyn; Junglen, Sandra; Tchouassi, David P. (Frontiers in Microbiology, 2024)
Culicoides biting midges (Diptera: Ceratopogonidae) are vectors of arboviral pathogens that primarily affect livestock exemplified represented by Schmallenberg virus (SBV), epizootic hemorrhagic disease virus (EHDV) and bluetongue virus (BTV). In Kenya, studies examining the bionomic features of Culicoides including species diversity, blood-feeding habits, and association with viruses are limited. In this study, adult Culicoides were surveyed using CDC light traps in two semi-arid ecologies, Baringo and Kajiado counties, in Kenya. Analysis of blood-fed specimens through polymerase chain reaction (PCR) and sequencing of cytochrome oxidase subunit 1 (cox1) barcoding region confirmed that midges had fed on cattle, goats, sheep, zebra, and birds. Cox1 barcoding of the sampled specimens revealed the presence of known vectors of BTV and epizootic hemorrhagic disease virus (EHDV) including species in the Imicola group (Culicoides imicola) and Schultzei group (C. enderleni, C. kingi, and C. schultzei). Culicoides leucostictus and a cryptic species distantly related to the Imicola group were also identified. Screening of generated pools (11,006 individuals assigned to 333 pools) by generic RT-PCR revealed presence of seven phylogenetically distinct viruses grouping in the genera Goukovirus, Pacuvirus and Orthobunyavirus. The viruses showed an overall minimum infection rate (MIR) of 7.0% (66/333, 95% confidence interval (CI) 5.5 -8.9). In addition, full coding sequences of two new iflaviruses, tentatively named Oloisinyai_1 and Oloisinyai_2, were generated by next-generation sequencing (NGS) from individual homogenate of Culicoides pool. The results indicate a high genetic diversity of viruses in Kenyan biting midges. Further insights into host-vector-virus interactions as well as investigations on the potential clinical significance of the detected viruses are warranted.